The resurgence of a Bolivarian militarism in the Andean region, interview with Germán Carrera Damas - Bustos, Guillermo (2016)
Germán Carrera Damas holds a Ph.D. in History from the Central University of Venezuela, where he served as a teacher and director of the School of History. He is also a professor at the University of Florida, in the United States. He currently chairs the drafting committee of the General History of Latin America and is a member of the international scientific committee for the new edition of the History of the scientific and cultural development of humanity, both under the editorial sponsorship of UNESCO.